PENGARUH BUDAYA ORGANISASI, SELF EFFICACY DAN SEMANGAT KERJA TERHADAP KINERJA KARYAWAN DIVISI PRODUKSI PT. MESKOM AGRO SARIMAS BENGKALIS - , Rio Jonnes M, Marpaung, Rezki Ananda , Samsir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to determine the effect of organizational culture, self-efficacy and morale on the performance of production division employees at PT. Meskom Agro Sarimas Bengkalis. The population is 70 people with a total sample of 70 people. The analytical method used in this study is quantitative descriptive with the Multiple Linear Regression Analysis technique using SPSS version 25. The results of this study indicate organizational culture (X1) has a significant effect on performance (Y), self-efficacy (X2) has a significant effect on performance (Y) , Work enthusiasm (X3) has a significant effect on performance (Y) with F count (75.390) > F table (2.74) and a significant 0.000 <0.05 means that simultaneously organizational culture, self-efficacy and morale have an influence on employee performance production division of PT. Meskom Agro Sarimas Bengkalis with an adjusted r squared value of 0.764 or 76.4%. Keywords: Organizational Culture, Self Efficacy, Work Spirit, Performance